Fördelning av en kostnad utifrån olika rättviseteorier - Lundin, Petter (2007)
The increasing road traffic in Sweden will require investments in the infrastructure that the tax withdrawal of today will not allow according to a new government report, SOU 2006:33. An existing willingness to pay for those investments has therefore become an alternative to increases in taxation to be able to cover the costs. A proposal to let the willingness to pay, alternatively increases in taxation that act proportional, decide how a cost is distributed can be said to be related, but not fully correspond, with different theories of justice described by Robert Nozick and John Rawls. It can therefore be interesting to see how the two different theories of justice are edified and how they distribute a joint cost. The aim of the first part of the thesis is to present and criticize Rawls' and Nozick's theories of justice in a common formulated economic model. The aim of the second part is to give a theoretical suggestion about how the two theories of justice distribute a joint cost for a road project. The method that will be used is literature studies of the theories of justice described by Rawls in "A Theory of Justice" and by Nozick in "Anarchy, State and Utopia", and also of other economic literature. The conclusion in the first part is that utilitarianism and Rawls´ theory of justice under special circumstances can seem to be closely related. They are contrasted to Nozick's theory of justice that instead is founded on the freedom to choose. Rawls' difference principle is further superior to the demand for Pareto efficiency, which means that a distribution of a resource that is not Pareto efficient can be desirable for a society. Nozicks theory of justice will however always lead to a Pareto efficient distribution of resources. Rawls is also an advocate for government control to achieve distributional justice, while Nozick instead is an advocate for a state that only protects against the violation of rights. The main criticism against Rawls' theory of justice is finally that it takes away all of the conditions for a human to make rational choices. The criticism against Nozick's theory of justice is instead that it can lead to situations with limitations of freedom for individuals to achieve different goals. The conclusion for the second part is that the proposal for the distribution of a cost from Rawls' difference principle leads to equal utility for all parties. The proposal for the distribution of a cost from Nozick's theory of justice comes instead from the freedom to choose. How the total cost is finally distributed is then decided after negotiation between the parties, where the power to negotiate for each party respectively will determine the end result.